Formulation, optimization, and in vitro characterization of dasatinib loaded polymeric nanocarriers to extend the release of the model drug - Adena S.K.R.; Matte K.V.; Kosuru R. (My University, 2025)
Objective: The present research aims to design, develop, optimize, characterize and evaluate dasatinib (DSB) loaded polymeric nanocarriers to treat chronic myeloid leukaemia (CML) by adopting a quality by design (QbD) approach. Methods: Risk assessment was performed by using failure modes and effects analysis, and optimization of nanoformulation was done by adopting 23 full factorial design. The optimized nanoformulation was characterized by different characterization techniques and evaluated by various in vitro studies. Results: Surface morphology and shape were found to be smooth and spherical. Stability study results revealed that the nanoformulation could be stored in all three storage conditions for safe and long-term use since it retained its pharmaceutical properties. Drug release was 32.06 % in the first 4 h and 79.34 % by the end of 48 h which infers a sustained-release pattern. The hemocompatibility results showed no sign of hemolysis. Cellular uptake study showed approximately 10 to 20-fold much higher intracellular fluorescence intensities of nanoformulation than DSB. Cytotoxicity results confirmed that when compared to the pure drug, the optimized nanoformulation have a potential cytotoxic effect in the treatment of CML since it exhibited a significantly more % growth inhibition. Cell apoptosis assay revealed that the nanoformulation could provide significant antileukaemia activity against K562 cells and further induce K562 cell death with a dose and time-dependent manner. Conclusion: The results of the characterization and evaluation studies showed that the developed nanoformulation offered significant advantages, making it a potential delivery system of DSB for more effective treatment of CML. © 2021 The Authors.